Fraudulence Detection in Fish Marketing of Bangladesh using DNA Barcoding (Journal of Bangladesh Academy of Sciences, 2017)
DNA barcoding, based on the sequencing of a short, standardized region of the cytochrome c oxidase subunit 1 (COI) gene has the potential to be a practical method for fish species identification in raw or processed fish products. The aim of this study was to identify the level of fraudulence in fish marketing particularly in super shops of Bangladesh. Different species of fish as whole or in fillet were collected from different supermarkets and local markets of Dhaka metropolis for examination. COI gene sequence was amplified using random primers (Fish F1, Fish F2, Fish R1 and Fish R2) and then compared with reference sequences from GenBank and BOLD (Barcode of Life Data Systems). The database was able to provide species matches of >85% sequence similarity for ten samples tested. The overall fraudulence was detected 80% but specifically for whole fish it was 85.71% and fraudulence for fish fillet was 66.67%. These naming discrepancies and ambiguities demonstrate that DNA barcoding can be a reliable tool for the detection of fish products mislabeling in Bangladesh. Therefore, it can be a useful tool for fraudulence control, law enforcement and guiding consumers to get rid of fish product fraudulence.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 17-27 2017